Baicalin improves isoproterenol-induced cardiac remodeling by regulating the Nrf2-dependent signaling pathway - Kai Qian; Li Song; Jia-Min Guo; Dan Fu; Jia Shi; Yu Ma; Zi-Jie Ge; Lei Li; Su-qin Zhang (BMC Cardiovascular Disorders)
Abstract Background Cardiovascular disease carries the highest mortality rate among diseases, and pharmacological interventions have limited efficacy. Baicalin (Bai) promotes biological metabolic processes, eliminates oxygen free radicals, and is anti-inflammatory. This study aimed to investigate the effect of Bai on the cardiac injury model induced by isoproterenol in mice. Methods and Result In this study, all groups except the control received intraperitoneal injections of isoproterenol (ISO) to induce a cardiac injury model, with the drug administered continuously for 14 days. hematoxylin and eosin staining and Masson’s trichrome staining revealed that Bai significantly mitigated ISO-induced pathological changes in mouse heart tissue and alleviated myocardial hypertrophy. Echocardiography assessments demonstrated that Bai preserved cardiac function in ISO-treated mice. Furthermore, our findings indicated that Bai activated the Nrf2 signaling pathway in vivo and in vitro. To delve deeper, mice were further treated with ML385 (ML) via intraperitoneal injection to inhibit the Nrf2 pathway. Results showed that ML385 blocked the cardioprotective effects of Bai in mouse heart tissue. Conclusion Bai protects against ISO-induced cardiac injury, and its mechanism is related to activating the Nrf2/HO-1 signaling pathway to regulate cardiac ferroptosis and improve cardiac remodeling.